Arthroscopic Posterior Capsular Release Improves Range of Motion and Outcomes for Flexion Contracture After Anterior Cruciate Ligament Reconstruction in Athletes - Joseph C. Brinkman, M.D; Jose M. Iturregui, M.D; M. Lane Moore, B.S., M.B.A; Jack Haglin, M.D; Adam Thompson, B.S; Justin Makovicka, M.D; Kostas J. Economopoulos, M.D (Elsevier, 2024)
Purpose: To assess outcomes of arthroscopic posterior capsular release among athletes for loss of terminal extension following anterior cruciate ligament (ACL) reconstruction. Methods: A retrospective review of prospectively collected data was performed for patients undergoing arthroscopic posterior capsular release for knee extension loss following ACL reconstruction between January 2014 and December 2019. Procedure indications included extension loss greater than 10° at least 3 months after ACL reconstruction that was refractory to physical therapy. Patients were included if they were involved in either high school or college athletics, had complete outcomes of interest, and had at least 2 years of follow-up. Prospectively collected outcomes included preoperative and postoperative measurement of knee extension, International Knee Documentation Committee score, Lysholm score, return to sport data, and complications. Results: Eighteen athletes with minimum 2 years of follow-up who underwent posterior capsular release following ACL reconstruction performed by a single surgeon were included in the analysis. Patients underwent surgery at an average of 16 weeks after ACL reconstruction. Knee extension improved an average of 13.8° at 2 years' follow-up (prerelease mean extension deficit 15.1°, postrelease mean extension deficit 1.3°, P < .005). Improvements in the International Knee Documentation Committee score averaged 21.7 at 6 months and 35.0 at 24 months, both of which were statistically significant (P < .001). Similarly, differences in Lysholm included a significant improvement of 23.0 and 34.2 at 6 months and 2 years, respectively (P < .001). In total, 77.8% returned to sport at an average of 9.8 months from their primary ACL surgery and 6.5 months following posterior capsular release surgery. No infections or neurovascular complications were observed. One patient required secondary release to achieve adequate extension. Conclusions: For athletes with persistent knee extension loss after ACL reconstruction, knee extension was significantly improved at 2 years following arthroscopic posterior capsular release. Substantial improvements in patient-reported outcomes also were seen. In addition, subjects demonstrated a high rate of return to sport and return to preinjury performance levels. Level of Evidence: Level IV, therapeutic case series.